The Effect of Financial Literacy and PT Pegadaian's Sadari Emas Event on Purchasing Decisions for Gold Savings Products at PKK Tulungrejo, Batu - Uki Yonda Asepta; Santi Widyaningrum; Valencia Cicilia Davina (Jurnal Ekonomi dan Bisnis Digital, 2023)
This study was conducted to determine the effect of financial literation and event marketing Sadari Emas PT Pegadaian on purchasing decisions for gold savings products. This research uses quantitative methods by distributing questionnaires to respondents offline. In this study using non-random sampling technique with purposive sampling method. The purpose of the study was to determine how much influence financial literacy and Sadari Emas PT Pegadaian marketing events have on purchasing decisions for gold savings products at PKK Tulungrejo, Batu. The results showed that there is a strong relationship between financial literacy and event marketing Sadari Emas PT Pegadaian on purchasing decisions for gold savings products. Based on the results of the calculation of the detrmination coefficient, it can be obtained that the value is 52%. So this shows that financial literacy and Event Marketing Sadari Emas PT Pegadaian have a 52% influence on purchasing decisions for gold savings products, so the remaining 48% is influenced by other factors not examined.